2011
DOI: 10.1088/0957-4484/22/6/065102
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanohorns accelerate bone regeneration in rat calvarial bone defect

Abstract: A recent study showed that carbon nanohorns (CNHs) have biocompatibility and possible medical uses such as in drug delivery systems. It was reported that some kinds of carbon nanomaterials such as carbon nanotubes were useful for bone formation. However, the effect of CNHs on bone tissue has not been clarified. The purpose of this study was to evaluate the effect of CNHs on bone regeneration and their possible application for guided bone regeneration (GBR). CNHs dispersed in ethanol were fixed on a porous poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…521524 MWCNTs have been reported by many research teams, including ours, to possess bone induction potential. 58,62,63,67,213,215,216,218,525,526 If conjugation with MWCNTs further improves the mechanical characteristics of PEEK and also induces osteogenesis, then MWCNT/PEEK composite will become an ideal interbody fusion material (Figure 13). …”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…521524 MWCNTs have been reported by many research teams, including ours, to possess bone induction potential. 58,62,63,67,213,215,216,218,525,526 If conjugation with MWCNTs further improves the mechanical characteristics of PEEK and also induces osteogenesis, then MWCNT/PEEK composite will become an ideal interbody fusion material (Figure 13). …”
Section: Discussion and Perspectivementioning
confidence: 99%
“…The extent of osteogenesis was greater under the membrane containing carbon nanohorns than under the membrane without the carbon nanohorns, showing that carbon nanohorns accelerated bone regeneration. 216 …”
Section: Present Status Of Research Into the Application Of Cnts As Bmentioning
confidence: 99%
“…Carbon-based nanosubstrates, such as carbon nanotubes, 13,14 carbon nanohorns, 15 carbon nanofibers, 16 and graphene, 17,18 have been investigated widely for stem cell therapies and tissue engineering platforms because of their unique physical, chemical, and mechanical properties. Graphene oxide (GO) in a two-dimensional honeycomb lattice of a carbon monolayer is obtained by oxidation and exfoliation of graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that carbon nanohorns (CNH; another carbon allotrope closely related to the fullerenes), fixated on a porous polytetrafluoroethylene membrane, were used for covering the calvarial bone defect in rats. The results showed the attachment of macrophages to CNHs and acceleration of newly formed bone regeneration in the presence of these nanoparticles [26]. …”
Section: Introductionmentioning
confidence: 99%